How does Modernity Taste? Tomatoes in the Societal Change from Modernity to Late Modernity - Lena Ekelund; Håkan Jönsson (Culture Unbound: Journal of Current Cultural Research, 2011)
The aim of this article is to discuss how changes in tomato food regulation, production and consumption, can be seen as part of a broader societal change from Modernity to Late Modernity. Based on evidence from the Swedish and European food systems we demonstrate how a system, which has been successfully managing development in food production for several decades by stressing rationality, homogeneity and standardization, is being challenged by a system that has adapted to, and also exploited, consumer preferences such as heterogeneity, diversity and authenticity. The article shows how tomato growers develop differentiation strategies, adapting to and cultivating this new consumer interest, and how authorities responsible for regulations of trade and quality struggle to adapt to the new situation. As the products become more diversified, taste becomes an important issue and is associated with a view that traditional and natural are superior to standardized and homogeneous products. The analytical approaches for the discussion come from two study areas: ethnological, and marketing and policy perspective, thus showing a multidimensional picture of a changing food system.